2015
DOI: 10.1021/acs.joc.5b02248
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Boron Complex-Promoted Asymmetric Diels–Alder Cycloaddition and Its Application in Natural Product Synthesis

Abstract: An efficient method for the asymmetric Diels-Alder cycloaddition of 2'-hydroxychalcones with acyclic or cyclic dienes has been successfully developed. The Diels-Alder cycloaddition is mediated by a chiral boron complex with VANOL, affording the corresponding products in high yields and with excellent diastereo- and enantioselectivities. This reaction enabled the enantioselective construction of cyclohexene skeletons crucial for the total synthesis of a number of Diels-Alder-type natural products (-)-nicolaioid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
69
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(78 citation statements)
references
References 53 publications
8
69
0
1
Order By: Relevance
“…Wulff and coworkers have reported a hydrogen-bonded complex of a boroxinate catalyst and a protonated iminium substrate. 26b We also found that treatment of crystalline 26 with diene 22 led to similar results, producing 24 in high enantioselectivity. 13 The latter result reinforces the involvement of borate complex 26 in the catalytic asymmetric DA cycloaddition, which is also supported by literature precedent.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Wulff and coworkers have reported a hydrogen-bonded complex of a boroxinate catalyst and a protonated iminium substrate. 26b We also found that treatment of crystalline 26 with diene 22 led to similar results, producing 24 in high enantioselectivity. 13 The latter result reinforces the involvement of borate complex 26 in the catalytic asymmetric DA cycloaddition, which is also supported by literature precedent.…”
supporting
confidence: 63%
“…Accordingly, we proposed that enantioselective [4+2] cycloaddition of chiral, racemic substrate 18 and dienophile 20 should efficiently deliver two natural products simultaneously utilizing a stereodivergent process. In our initial studies, 25 we found that borate complexes derived from chiral 1,1′-bi-2-naphthol (BINOL) 5b,26 could be used in catalytic, enantioselective [4+2] cycloadditions of 2′-hydroxychalcones. A two-dimensional screen was conducted using a number of borates (B(OPh) 3 , tris( p -chlorophenyl), tris(pentafluorophenyl), and tris(hexafluoroisopropyl) borate) and BINOL ligands.…”
mentioning
confidence: 99%
“…雷晓光课题组 [66] 致力于通过不对称 Diels-Alder 反 应合成策略, 高效构建 Diels-Alder 类型天然产物的环己 烯核心骨架, 最终实现对于包含此类骨架结构天然产物 的全合成. 2'-羟基查尔酮为亲双烯体的不对称 Diels-Alder 反应研究工作中, 课题组成员李霞等 [67] 研究发现, 本文概述 α,β-不饱和羰基化合物为亲双烯体的不对 称 Diels-Alder 环合反应, 亲双烯体底物包括 α,β-不饱和 酮、醛类和羧酸衍生物等. 目前报道的不对称催化体系 大多通过降低亲双烯体 LUMO 轨道能量, 从而降低与 双 烯 HOMO 轨 道之间能量 差, 完成正 电子需求 的 Diels-Alder 反应和杂 Diels-Alder 反应.…”
Section: R-70unclassified
“…Approaches to the total synthesis of cylohexenyl chalcones derived from myrcene have rarely been described in the literature, but all of the reported approaches involve a bioinspired Diels–Alder cycloaddition for the construction of the cyclohexenyl core. Although these approaches are elegant and original, most of them are limited to 2′‐hydroxychalcones as substrates . Two of the published strategies were developed in asymmetric versions by using either chiral boron complexes as catalysts or camphor α′‐hydroxyenones as substrates .…”
Section: Introductionmentioning
confidence: 99%
“…Although these approaches are elegant and original, most of them are limited to 2′‐hydroxychalcones as substrates . Two of the published strategies were developed in asymmetric versions by using either chiral boron complexes as catalysts or camphor α′‐hydroxyenones as substrates . Two other more straightforward methods use thermal Diels–Alder cycloaddition reactions,, but the temperatures required for these processes (>120 °C) are incompatible with complex substrates.…”
Section: Introductionmentioning
confidence: 99%